Globalization, industrialization and labour markets in China - Zhang, M.; Rasiah, R. (Taylor & Francis, 2015)
China's experience with globalization is still contested. This paper seeks to examine the impact of global integration and industrialization on labour markets in China. The evidence shows that rising trade and flows of foreign direct investment has not only quickened industrialization and structural change but it has also stimulated a rapid rise in overall and manufacturing real wages. The government's framework of absorbing marketization while maintaining planning control through decentralization has been critical in the development of technological capabilities in manufacturing. Although the nature of economic development after reforms has also widened regional inequalities with the Eastern coastal provinces enjoying higher growth and structural change than the Western and other inland provinces, rising wages suggest that the material conditions of the majority of workers in China have improved.